Pendampingan Guru dalam Membangun Minat Baca Al-Qur’an di Kecamatan Siman Kabupaten Ponorogo - Ashari, Riza; Lahuri, Setiawan Bin; Harris, Jaudat Iqbal; Alafianta, Novan Fatchu; Nurcholis, Agung (Penerbit Widina, Widina Media Utama, 2025)
This community service activity focuses on assisting Quran Education Center (TPA) teachers in Siman District, Ponorogo Regency, with an emphasis on increasing students' interest in reading the Quran according to the discipline of tajweed. The objective of this community service is to address the challenges faced in Quran learning in the area, including the need for curriculum adjustments and suitable teaching methods. The assistance was carried out by five educators from Darussalam Gontor University over a specific period and involved 16 TPAs around the campus. The implementation methods included training in Reading, Storytelling, and Singing (BCM), Tahsin Qiro'ah training, inter-TPA competitions, art performances, and TPA graduation ceremonies (Quran khataman). The results showed an increase in students' interest, talent identification, talent development monitoring, as well as academic achievements such as Quran memorization and tajweed knowledge. Another significant outcome of this community service is providing a comprehensive overview of efforts to improve the quality of Quranic education in TPAs, emphasizing the importance of combining engaging learning approaches with the application of tajweed knowledge. Activities such as inter-TPA competitions and art performances were integrated to stimulate learning enthusiasm and foster Islamic character among the younger generation.ABSTRAKKegiatan pengabdian masyarakat ini berupa kegiatan pendampingan pengajar Taman Pendidikan Al-Quran (TPA) di Kecamatan Siman, Kabupaten Ponorogo, dengan fokus pada peningkatan minat santri dalam membaca Al-Quran sesuai dengan disiplin ilmu tajwid. Tujuan dari pengabdian masyarakat ini adalah tantangan yang dihadapi dalam pembelajaran Al-Quran di daerah tersebut, termasuk kurikulum dan metode pembelajaran yang perlu disesuaikan. Pendampingan dilakukan oleh lima tenaga pendidik Universitas Darussalam Gontor selama periode tertentu dan melibatkan 16 TPA di sekitar kampus. Metode pelaksanaan pendampingan mencakup pelatihan Baca, Cerita, dan Menyanyi (BCM), pelatihan Tahsin Qiro'ah, perlombaan antar TPA, pentas seni, dan wisuda TPA (khataman Al-Quran). Hasil kegiatan menunjukkan peningkatan minat santri, identifikasi bakat, pemantauan perkembangan bakat, serta pencapaian akademis seperti hafalan Al-Quran dan pengetahuan tajwid. Hasil penting lainnya dari kegiatan pengabdian ini yaitu memberikan gambaran komprehensif tentang upaya meningkatkan kualitas pendidikan Al-Quran di TPA, menekankan pentingnya memadukan pendekatan pembelajaran yang menyenangkan dengan penerapan ilmu tajwid. Kegiatan seperti perlombaan antar TPA dan pentas seni diintegrasikan untuk merangsang semangat belajar dan membangun karakter islami pada generasi muda.